Craftsmen training issues for Lithuania in the middle of the nineteenth century - Endzinas, A. (Psichologija, 1964)
Vilnius University attached great importance to practical handcrafted and crafts skills training at the educational institutions in the Vilnius School District. Reactionary school regulations made it possible to teach a trade in 1828, but after political events, the suppression of the 1830–1831 uprising, only half of the reactionary provisions were implemented in Lithuania. Handiwork and craftsmanship were not given the attention or special training in these subjects require. This is why only the 21st folk school in the Vilnius School District Governorate taught craftsmanship in the 19th century.Economic developments in the country, especially in 1860 when Russian exports and imports were moving primarily through Lithuanian lands by land and river, rail and road construction required a larger number of workers with craft work skills. In the absence of craft schools, rural and urban artisans, individuals trained by craftsmen or trained by their parents, the military, or self-taught people filled in the ranks of such workers. Governorate state property agencies tried to get orphans and boys from poor families into craftsmen apprenticeships. A craftsman would take on an apprentice with room and board for free provided the apprentice would learn at his side for a given period. There was a relatively good number of such apprentices learning the trade this way, 357 in the Vilnius Governorate in 1853. Due to long military service, most of the returnees were not able-bodied and couldn't work hard. Furthermore, the skills they'd acquired there were not very diverse.So what craftsmen demand of them amounted to a line of work they could live with.  Pushing poor and landless peasants' children into craftsmanship partly contributed to solving social problems. The 1853 craftsmen regulations also helped. The 19th century writer Motiejus Valančius encouraged learning craftsmanship in "Palangos Juzė" (named for a hotel) and "Paaugusių žmonių knygelė" (The Little Book of Older Folks). He said that young people learning a trade need to let their knowledgeable boss be in charge. But the craft must be chosen with regard to adolescent inclinations. Interest in learning crafts began to grow. Individual apprenticeship training opportunities in master workshops were insufficient to meet demand. The country's economic development required linking the acquisition of practical skills with theoretical preparation.
Keywords: history of pedagogy and craftsmanship training.